Journeys in Evangelical America - Bjerre-Poulsen, Niels (American Studies in Scandinavia, 1992)
- Nancy T- Ammerman's 'Bible Believers: Fundamentalists in the Modern World'- James Davison Hunter's 'Evangelicalism: The Coming Generation'- Randall Balmer's 'Mine Eyes Have Seen the Glory: A Journey Into the Evangelical Subculture in America'- Michael D'Antonio's 'Fall From Grace: The Failed Crusade of the Christian Right'